Associations of estimated Δ-5-desaturase and Δ-6-desaturase activities with stroke risk factors and risk of stroke: the Kuopio Ischaemic Heart Disease Risk Factor Study. Issue 4 (6th April 2017) - Daneshmand, Roya; Kurl, Sudhir; Tuomainen, Tomi-Pekka; Virtanen, Jyrki K.
Abstract: Stroke is a leading cause of morbidity and mortality. The role of PUFA in reducing the risk of stroke is uncertain. The concentrations of PUFA in the human body are determined both by dietary intake and by activities of desaturase enzymes. Desaturase enzymes have been associated with chronic diseases, but little is known about their association with stroke risk. We investigated the associations of Δ-6-desaturase (D6D) and Δ-5-desaturase (D5D) activities with stroke risk factors and risk of stroke among 1842 men from the prospective, population-based Kuopio Ischaemic Heart Disease Risk Factor Study, aged 42–60 years and free of CVD at baseline in 1984–1989. ANCOVA and Cox regression models were used for the analyses. Whole serum desaturase activities were estimated as product:precursor ratios – γ -linolenic acid:linoleic acid for D6D and arachidonic acid:dihomo- γ -linolenic acid for D5D. Higher D6D activity was associated with higher systolic and diastolic blood pressure, BMI, serum insulin and TAG concentrations and worse homoeostatic model assessment (HOMA) indices. In contrast, higher D5D activity was associated with lower systolic and diastolic blood pressure, BMI, serum insulin, LDL-cholesterol, TAG and C-reactive protein concentrations, higher HDL-cholesterol concentration, and better HOMA indices. During the mean follow-up of 21·2 years, 202 stroke cases occurred. Neither D6D activity (multivariable-adjusted extreme-quartile hazard ratios (HR) 1·18; 95 % CI 0·80, 1·74) nor D5D activity (HR 1·06; 95 % CI 0·70, 1·60) were associated with stroke risk. In conclusion, higher D5D activity was favourably associated and higher D6D activity unfavourably associated with several stroke risk factors, but not with the risk of incident stroke.